2001
DOI: 10.1046/j.1523-1755.2001.00783.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of stem cell factor and mast cells in the progression of chronic glomerulonephritides11See Editorial by Eddy, p. 375

Abstract: MCs as an infiltrating hematopoietic cell and its growth factor (SCF) seem to be up-regulated in glomerulonephritis, and may play a role in the development of renal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…In the study by El-Koraie et al, 22 mast cells and their associated growth factor (SCF) and receptor (c-kit) were present within the interstitium of scarred human kidneys and played a role in the initiation and progression of renal interstitial fibrosis. Frangogiannis et al 23 reported an increase in the number of mast cells in areas of collagen deposition and proliferating cell nuclear antigen expression and concluded that mast cells played an important role in myocardial remodeling and fibrosis after myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by El-Koraie et al, 22 mast cells and their associated growth factor (SCF) and receptor (c-kit) were present within the interstitium of scarred human kidneys and played a role in the initiation and progression of renal interstitial fibrosis. Frangogiannis et al 23 reported an increase in the number of mast cells in areas of collagen deposition and proliferating cell nuclear antigen expression and concluded that mast cells played an important role in myocardial remodeling and fibrosis after myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…32 Evidence for a role of SCF in human airway disease was supported by studies demonstrating increased SCF expression in nasal polyps of asthmatics and allergic rhinitis patients. 33,34 Additionally, SCF has been implicated as a potential mediator in fibrotic diseases in the kidney and intestine. 34 -37 Recently, the role of SCF has been verified using a chronic Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells, a rare cell population in healthy kidneys, increase in chronic inflammation and fibrosis, including that of allografts in which their numbers correlate with renal injury (48)(49)(50)(51). Most studies have suggested that a reduction of mast cells, or their typical enzyme chymase, increases fibrosis (52)(53)(54)(55)(56), whereas others suggest the opposite (57,58).…”
Section: The Role Of Immune Cellsmentioning
confidence: 99%